Controllable Preparation of Carbon Materials with Different Morphologies Assisted by Molten Salt Electrolysis. (3rd December 2019) - Luo, Hua-Jiang; Xue, Yun; Zheng, Yang-Hai; Yan, Yong-De; Ma, Fu-Qiu; Zhang, Mi-Lin; Yin, Tai-Qi; Gao, Fan; Qiu, Min
Abstract : This work described the electrochemical synthesis of carbon material with different morphologies on the Ni electrode by controlling the temperature in Li2 CO3 -Na2 CO3 melt. The electrochemical behaviors on an inert W electrode and an active Ni electrode were analyzed by cyclic voltammetry at 600°C. The results indicated that more reduction peaks were observed on Ni wire working electrode than W one. The XRD analysis of the samples synthesized by potentiostatic electrolysis at −1.4, −1.7 and −2.0 V for 3 hours proved that the reduction peaks were related to the deposition of carbon. The carbon materials were also prepared at 550, 600, 650, and 700°C on Ni sheet electrodes by galvanostatic electrolysis at 0.3 A. The microstructure and micro-zone chemical analysis of carbon materials were characterized by SEM, TEM, Raman spectroscopy and XRD. Amorphous and various nanostructures were revealed by electron microscopy in carbon samples deposited under different process conditions. The surface porosity of carbon at different electrolysis temperatures was investigated by N2 adsorption-desorption isotherm measurement. The specific surface area of carbon decreases with the increase of the reaction temperature. The thermal stability of the carbon was analyzed by thermogravimetry, indicating that it is completely oxidized below 480°C.